PI3K in T Cell Adhesion and Trafficking - Johansen, Kristoffer H.; Golec, Dominic P.; Thomsen, Julie H.; Schwartzberg, Pamela L.; Okkenhaug, Klaus (Frontiers in Immunology, 2021)
PI3K signalling is required for activation, differentiation, and trafficking of T cells. PI3Kdelta, the dominant PI3K isoform in T cells, has been extensively characterised using PI3Kdelta mutant mouse models and PI3K inhibitors. Furthermore, characterisation of patients with Activated PI3K Delta Syndrome (APDS) and mouse models with hyperactive PI3Kdelta have shed light on how increased PI3Kdelta activity affects T cell functions. An important function of PI3Kdelta is that it acts downstream of TCR stimulation to activate the major T cell integrin, LFA-1, which controls transendothelial migration of T cells as well as their interaction with antigen-presenting cells. PI3Kdelta also suppresses the cell surface expression of CD62L and CCR7 which controls the migration of T cells across high endothelial venules in the lymph nodes and S1PR1 which controls lymph node egress. Therefore, PI3Kdelta can control both entry and exit of T cells from lymph nodes as well as the recruitment to and retention of T cells within inflamed tissues. This review will focus on the regulation of adhesion receptors by PI3Kdelta and how this contributes to T cell trafficking and localisation. These findings are relevant for our understanding of how PI3Kdelta inhibitors may affect T cell redistribution and function.